THE USE OF MODERN TECHNOLOGIES IN THE SYSTEM OF LOCALIZATION AND MANAGEMENT OF MOBILE ENTITIES IN REAL TIME (Perner's Contacts, 2011)
The article presents the outcomes of the project entitled "The localization and management of mobile entities in real time during crisis management in transportation". This research and development project has been conducted in support of sustainable development of transportation and sponsored by the Ministry of Transport of the Czech Republic. The aim of the project was to design the system of localization and management of mobile resources used in managing the crisis situations. The management system is based on new communication technologies, which allow managerial and executive components of the system high mobility and better way of communication. The project was to create a more effective operational management system of mobile entities in emergency situations when the development of crisis situation requires an immediate change in management.
Keywords: localization; mobile sources; communications technology; crisis situations; transport